PENERAPAN PENDEKATAN MATEMATIKA REALISTIK (PMR) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 010 PEJANGKI KECAMATAN BATANG CENAKU - Muslim '; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study titled realistic mathematical approach to improve learning outcomes class IV of SD Negeri 010 Pejangki Kecamatan Batang Cenaku. This study aims to improve learning outcomes, and the performance of teachers in mathematics in the fourth grade SD Negeri 010 Pejangki Kecamatan Batang Cenaku. The method used is the Classroom Action Research (PTK). The research sample numbering 18. The results showed that in the first cycle the average value of student learning outcomes 77.78 category (B) with classical learning completeness 72%. Activities in the learning process the first meeting with the 75% category (B), the second meeting of 81.25% with a category (AB), and the value of the activity the teacher first meeting with the 78% category (B), meeting 86% with category II (AB), In the second cycle, the average value of student learning outcomes 91.72% category (AB) with classical learning completeness 100%, the activity of students in the learning process the first meeting of 89.58% with a category (AB), the second meeting of 95.83% with category (AB), and the value of the activity of the first meeting of teachers 89% (AB), the second meeting of 94.44% with a category (AB). The results showed an increase from the first cycle to the second cycle. Based on the results obtained, it can be disimpulksn that PMR approach is proven to improve student learning outcomes, student activities, and the activities of teachers. Keywords: Realistic Mathematics Approach, learning outcomes